Continuity analysis of the “Programa de Recuperação e Desenvolvimento da Bacia da Pampulha” (PROPAM) (Research, Society and Development, 2020)
That article intends to show an analysis of the continuity of PROPAM based on the evolution of the management of this program, with a focus on the current legislation and the performance of corporations and people who represent them.A continuous public policy/program is the one that in the transition period of governments is considered by the new government installed as State policy and that does not change its objectives, regardless of the discourse. Considering that environmental policies become ineffective or inefficient when discontinued, this work intends to carry out an analysis of PROPAM's continuity, seeking its interpretation through document analysis, interview with actors and participation in a public hearing, with the aim of to answer whether changes in management and legislation, guided by the change of actors, interfered with its continuity. When analyzing the trajectory of PROPAM, it is observed that the Program is continuous in terms of public action because it is still active after 20 years, resisting government transitions. It was also possible to see that its continuity is ensured by a set of factors, among which its regulation through Municipal Law, which endorses its financial and institutional apparatus and prevents the mischaracterization of the policy; and the participation of some actors that represents a motivational apparatus for the continuity of the Program. However, PROPAM presents itself as an unstable program, especially since 2013, when it left the focus of government agendas, which fostered the creation of a new program, with similar objectives and less restrictive parameters.